Platelet aggregation and lipoprotein levels in a patient with familial hypercholescholesterolemia after selective LDL-apheresis - Pares, Madalena Nunes da Silva; D’Amico, Elbio Antonio; Kutner, José Mauro; Chamone, Dalton de Alencar Fischer; Bydlowski, Sergio Paulo (São Paulo Medical Journal, 1997)
Platelet aggregation was studied in a patient with familial hypercholesterolemia immediately after aphereis selective for low-density lipoprotein (LDL), a lipid-lowering procedure.This treatment reduced plasmatic levels of total and LDL-cholesterol, apo B, and triglyceride. Increased platelet aggregation was reduced immediately after the apheresis in whole blood as well as in platelet-rich plasma. However, aggregation in washed platelets remained unchanged after LDL-apheresis. In conclusion, in this patient reduction of LDL-cholesterol improved platelet function in the very short term.